Value-based orientations as a normative-regulatory mechanism for the formation of professional worldview of future music teachers - Tkach, Mariia M.; Oleksiuk, Olga M. (Linguistics and Culture Review, 2021)
The transition period of modern society can be observed in various aspects, particularly in the value-normative one. The study of the Genesis of the formation of personality’s value-based orientations in the current conditions of reforming educational sector in Ukraine and its integration into the European Higher Education Area are becoming prioritized. The research methodology is complex, combining theoretical and empirical methods. Theoretical study of the problem of values in philosophical-historical and psychological-pedagogical discourses creates a methodological basis for expanding the subject field of interdisciplinary branches of scientific knowledge: pedagogical axiology and philosophy of music education. The interdisciplinary context of the conceptual range of these disciplines makes it possible to modernize the value-based orientation in the content of art education. The problem of spiritual and value-based formation of the personality by means of music is actualized, which creates the prerequisites for the formation of a phenomenon of holistic professional worldview of future music teachers. The analysis of structural components of the outlined phenomenon shows that the normative and regulatory basis of professional worldview is a system of value-based orientations of the individual.